Enhancing the Poetry Appreciation Ability Through Process Approach - Waliyudin, Waliyudin; Nashruddin, Nashruddin; Roslina , Roslina (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
The aim of this classroom action research is to increase students’ ability to appreciate poetry through process approach. Data is collected through observation and analysis of test result. This research was conducted in 2 cycles on 30 students of the 8th grade at SMP Dirgantara Makassar in the Indonesian language lesson. The data obtained was reviewed, reduced based on the research objective, presented, and ended with conclusion. The research results show that students’ ability to appreciate poetry can be enhanced by using process approach in language learning. It is proven by the increase of students’ learning outcome. The average score of students’ test result in the first evaluation was 70, and in the second evaluation in the end of the 1st cycle, it increased to 75. From 30 students, 12 scored below the completeness criteria (80), with the completion percentage was only 60%. In the 2nd cycle, the average score of students’ test result increased to 85. The completion percentage increased to 79%. The observation result also showed an increase in attitude, activeness, and enthusiasm of students in learning, and students’ understanding of the content of poetry, from the 1st cycle to the 2nd cycle.